Let's check the student's steps in solving the equation \(4(2-3x) = x - 2(2x + 1)\) and verify if they are correct.
-
Start with the given equation:
\[ 4(2 - 3x) = x - 2(2x + 1) \]
-
Distribute on both sides:
- Left side:
\[ 4 \cdot 2 - 4 \cdot 3x = 8 - 12x \]
- Right side:
\[ x - 2(2x + 1) = x - (4x + 2) = x - 4x - 2 = -3x - 2 \]
Now we rewrite the equation:
\[ 8 - 12x = -3x - 2 \]
-
The student's noted equation after the second step was \(8 - 3x = -3x - 2\), which is incorrect since it simplifies to:
\[ 8 - 12x = -3x - 2 \]
-
Let us solve \(8 - 12x = -3x - 2\):
Rearranging the equation:
- Add \(12x\) to both sides:
\[ 8 = 12x - 3x - 2 \]
- This simplifies to:
\[ 8 = 9x - 2 \]
- Now, add \(2\) to both sides:
\[ 8 + 2 = 9x \]
\[ 10 = 9x \]
- Finally, divide both sides by \(9\):
\[ x = \frac{10}{9} \]
So, the solution to the equation is:
\[ \boxed{\frac{10}{9}} \]
In conclusion, the student's steps contain an error in the transformation of the equation, and the correct solution is \(x = \frac{10}{9}\).